Lacuna - Tng, Gabriel Yue Hao (2017)
Lacuna, the name of my team’s animation, will be the subject of this FYP (Final Year Project) Report. The film is a science-fiction/drama of a mecha pilot who must learn to trust her apprentice. In essence, the story is a light-hearted animation that draws on themes normally found in buddy-cop films. As such, everything from the colour keys to the character designs were made to reflect that fact. It was essential we conveyed a sense of adventure and light-hearted fun that every one of all ages could enjoy. This report chronicles the production of Lacuna, from script to finished film. It will delve into the myriad difficulties the team faced, from story development to successfully hybridizing 2D and 3D animation. In the case of the latter, that proved to be especially challenging given it was uncharted territory for us. Lastly, the report will talk about the eventual solutions we discovered to these problems.